Bile-derived exosome noncoding RNAs as potential diagnostic and prognostic biomarkers for cholangiocarcinoma - Pan, Yan; Shao, Shijie; Sun, Hang; Zhu, Huafeng; Fang, Haixing (Frontiers in Oncology, 2022)
Background: Cholangiocarcinoma (CCA) is one of the most aggressive malignancies, lacking novel diagnostic and prognostic biomarkers. Exosome noncoding RNAs (ncRNA) were previously proposed as a potential source of biomarkers in several cancers. This study aimed to interpret the value of specific bile-derived ncRNA as predictors for early diagnosis and prognosis of CCA. Methods: We recruited 100 patients who received endoscopic retrograde cholangiopancreatography at our hospital for bile duct obstruction due to CCA (n = 50) and biliary stone (n = 50). They were further divided into training set and validation set (3:2). A panel of CCA-specific ncRNAs including 5 miRNAs (PMID: 30165035) and 2 lncRNAs (PMID: 29050258) were detected in both serum and bile exosomes. The diagnostic accuracy was assessed using the area under the receiver operating characteristic curve. Logistic analysis was used to classify the potential predictors of CCA and further establish the diagnostic model. Results: Exosomes were successfully collected from bile and serum. Exosomal miR-141-3p, miR-200a-3p, miR-200c-3p in serum and bile, as well as miR-200b-3p and ENST00000588480.1 in bile showed AUCs of >0.70 in the diagnosis of CCA. Bile exosomal miR-200c-3p displayed the best diagnostic value with the AUC of 0.87. The combination of serum CA19-9 into the model could increase the AUC to 0.906. Bile exosomal miR-200a-3p and miR-200c-3p were found to be independent predictors of CCA. Among exosomal ncRNAs in human bile and blood, 3 (serum and bile exosomal miR-200c-3p, bile exosomal miR-200a-3p) showed significant value in predicting cancer recurrence and 1 (serum exosomal miR-200c-3p) had great predictive ability of cancer death. High levels of serum exosomal miR-200c-3p showed unfavorable tumor-free survival and overall survival. Conclusion: The bile exosomal miR-200 family, particularly miR-200c-3p, was verified to be a potential biomarker for the early detection of CCA. The diagnostic ability of exosomal ncRNAs in human bile is better than that in blood. Moreover, high levels of bile exosomal miR-200a-3p, miR-200c-3p, and serum exosomal miR-200c-3p represented adverse clinical outcomes.